Standard of living in European Union countries - Topolewski, Łukasz; Topolewska, Kamila (Ekonomia i Prawo. Economics and Law, 2023)
Motivation: Researchers have been concerned with the issues related to the differences among economies for many years. The level of differentiation is an important matter as excessive economic and social differences among the states may lead to limited scope of integration processes, which in turn determine the development rate of regions. Due to how significant this issue is, it was decided that the level differentiation of the standard of living of the population in selected European Union countries ought to be investigated. Aim: The purpose of the article is to compare the standard of living in the countries of the European Union, with particular emphasis placed on the countries that joined the Union in 2004. The authors try to answer the question whether the economic policy pursued by the EU achieves the intended effect. A synthetic measure was constructed to measure the standard of living, taking into account various aspects of life. The time scope of the study covers the period of 2005–2020. The choice of a specific time frame was dictated by the expansion of the number of European Union members in 2004 and the availability of data. Therefore, the analysis covered the countries of the European Union post 2005 (excluding Great Britain). Data were obtained from Eurostat. Results: Taking into account the values of the synthetic variable, it may be claimed that one the one hand, the standard of living in the countries is increasing, and on the other hand, the disparity between countries is decreasing. Therefore it should be noticed, that the economic policy pursued by the European Union achieves the intended effect.